Pelaksanaan Supervisi Bimbingan Konseling dalam Meningkatkan Keterampilan Layanan Konseling Guru BK SMA Kabupaten Rejang Lebong - Desty Kurniati; Tina Musyofah; Aji Prayetno Ojil (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2021)
Mastery of counseling service skills for counseling teachers always needs to be done to improve the professionalism and quality of counseling guidance services in schools. One way to improve the skills of counseling teachers is through the supervision of counseling guidance. This study aims to describe the guidance and counseling teachers' understanding of the skills they have in carrying out counseling services and to describe the implementation of counseling guidance supervision activities at SMA Rejang Lebong. This research is a quantitative descriptive study. The population of this study was all high school counseling teachers in Rejang Lebong. The results showed that some of the skills often used in counseling services were questioning skills, providing support and reinforcement, listening, closing, empathy, clarification, problem-solving, focusing, and encouraging skills. While skills that are rarely or not yet mastered include focusing, paraphrasing, confrontation, opening up, and reframing skills. The results of the evaluation of the counseling guidance supervision activities showed that 80.73% of the supervisors said they had understood, mastered, and implemented several counseling service skills taught by supervisors in providing counseling services in schools, and only about 19.27% said they had not mastered and had not fully implemented the skills taught by a supervisor.